Włocławska Kapituła Katedralna na tle aktualnych norm prawnych odnośnie kapituł kanonickich - Gręźlikowski, Janusz (Prawo Kanoniczne, 2008)
The Chapter Cathedral of Włocławek its beginning go back first half of XII centuries and justly be numbered to the oldest chapter in Poland. Her start to go back Chapter of Kruszwica. The Chapter of Włocławek entry in qualifications of the Chapter of Kruszwica consequently transfer the capitol of diocese from Kruszwica to Włocławek. The Chapter of Włocławek come into being about 1148 years. Her history is reach and testify her signify in life of the Włocławek Church the past, in particular assistance the bishop in management of diocese. The change in canon law after the Council of Watykański II and the next in the Code of Cannon Law from 1983 years results that the law statutes of chapters – also Włocławskiej – undergo radical change. The Chapter stop was the assist organ of dioceses bishop in management of dioceses, while stay her decision and consultative character chapter stand the council of priest meritorious for dioceses. The dignity of canon should be grant to priests distinguish honest life, virtue, science, zeal and care about Church. In new law reality the Chapter Cathedral of Włocławek, though destitute now most ancient qualification and competence, lake important element in structure of Włocławskiego and Polish Church. Testify about her statutory law, assignments obligations and also fact that in Poland not destroy chapters but reactivate old and create new council of chapters.